In Vitro Antimicrobial Effect of Virgin Coconut (Cocus nucifera L.) Oil Against Streptococcus mutans - Baltazar, Bernadine P.; Formales, Aurora Patricia R.; Fransisco, Marc Vincent P.; Tonel, Anna Lorraine H.; Rebueno-Santos, Jessica K. (Manila Department of Community Dentistry, University of the Philippines Manila, 2019)
INTRODUCTION: Dental caries affects 87% of Filipinos (DOH Survey, 2011). It is still one of the most prevalent oral health problems and the leading cause of tooth loss in the Philippines. The pathogenic bacteria associated with dental caries is Streptococcus mutans which is a Gram positive anaerobic bacterium. Virgin coconut oil, which is a locally available product in the Philippines has varying results regarding its antimicrobial activity against Gram-positive bacteria. This study aimed to determine the antimicrobial effect of virgin coconut oil against Streptococcus mutans.
METHODS: A total of 35 Mueller Hinton agar plates streaked with inoculum of Streptococcus mutans (ATCC 25175) were used as media for the Kirby Bauer Disk Diffusion Test. Each plate was divided into three areas for the placement of three 6mm filter paper disks each containing 25 microliters of the test materials. After 48 hours of incubation at 37o Celsius, the zones of inhibition were measured using a Boley gauge and recorded in millimeters. Descriptive statistics (mean and standard deviation) were computed for each of the materials to find their measures of central tendencies and averages of the data. Measures of Central Tendency and One-way Analysis of Variance (ANOVA) were used to analyze the data. Dunnett's Test was then used as the Post Hoc analysis using the ANOVA results.
RESULTS: The means and standard deviations for each material were as follows: for Virgin Coconut oil it was 9.06 ± 3.63 mm, for distilled water it was 0.46 ± 1.58 mm, and for chlorhexidine it was 22.93 ± 9.30 mm. P-values obtained when comparing virgin coconut oil to distilled water and chlorhexidine were both significant with values less than 0.05 (both values were < 0.001) when power is set to 80%.
CONCLUSION: The virgin coconut oil was able to produce a zone of inhibition on the blood agar plates which was statistically significant when compared to that of distilled water and chlorhexidine. The results had a directionality in which the results favored virgin coconut oil more than the distilled water, but less than the chlorhexidine. It can be concluded that virgin coconut oil inhibited the growth of Streptococcus mutans, as indicated by the presence of a zone of inhibition. But these results are limited because the study only used one bottle of each of the materials; and the sample size is small. Knowing this could pave the way for future research to incorporate virgin coconut oil in existing materials such as toothpastes or mouth rinses.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Dental caries; Streptococcus mutans; Virgin coconut oil; Kirby Bauer Disk Diffusion Test